ANALYSIS OF THE INFLUENCE OF QUALITY OF SERVICES AND SOCIAL ASSISTANCE ON COMMUNITY SATISFACTION (CASE STUDY IN SOCIAL ASSISTANCE RECIPIENT MSME ACTORS IN THE CITY OF HIGH CLUB) - CANDRASA, Limega (Universitas Efarina, 2022)
This study aims to determine the Analysis of the Effect of Service Quality and Social Assistance on Community Satisfaction (Case Study on Social Assistance Recipients in Tebing Tinggi City). The research method used is a quantitative method using the help of SmartPLS 3.0, which is collected from the results of distributing questionnaires to as many employees as 97 respondents. The analytical method used in this research is to use an instrument test, namely the validity and reliability test of the measurement model evaluation (outer model), the evaluation of the structural model (inner model), the analysis of the coefficient of determination (R2 ), hypothesis testing, namely the T test and F test. The results of SmartPLS in this study, namely the service quality variable (X1) has an effect on the community satisfaction variable (Y), the social assistance variable (X2) has no effect on the community satisfaction variable (Y), the service quality variable (X1) and social assistance (X2) has a significant effect. simultaneously on community satisfaction (Y).